‘Nothing About Us Without Us’: exploring benefits and challenges of peer support for people with disability in peer support organisations – protocol paper for a qualitative coproduction project - Catherine Walsh; David Yang; Meredith Tavener; Julie Duong; Shaylie Pryer; Arron Fitzpatrick; Julie Magill; Sarah Simmonds; Owen Baird-Peddie; Farhana Rahman; Carrie Hayter (BMJ Open)
Introduction One in six people live with disability in Australia with higher levels of disability of people from diverse communities, such as those with culturally and linguistically diverse (CALD) backgrounds. In Australia, CALD refers to people from diverse ethnicity and cultures, nationalities, societal structures and religions that may or may not speak a language other than English. This study employs researchers with lived experience of disability and peer support to study the impact of peer support for people with disability, including people from CALD backgrounds, in two peer-led organisations in New South Wales (NSW) Australia.Methods and analysis This study uses participatory action research and inclusive research design with researchers with lived experience, having lived experience of disability and a peer in the disability community, leading the research.Over three years, three different groups will be recruited through Community Disability Alliance Hunter (CDAH) and Diversity and Disability Alliance (DDAlliance): (1) peers with disability, (2) peer leaders with disability and (3) researchers with lived experience of disability and peer support. Data collection and creation methods include semistructured interviews, surveys and focus groups. Qualitative data will be analysed using thematic analysis through the lens of the researchers with lived experience.Ethics and dissemination Ethical approval was granted by the University of Newcastle Human Research Ethics Committee (Approval No: H-2021-0088). Dissemination includes peer-reviewed publications, presentations at local, national and international conferences and written reports for user-led organisations, disability service providers, disability agencies and people with disability.